BIMTEKS PENDAMPINGAN PENYUSUNAN MODUL AJAR KURIKULUM MERDEKA BELAJAR BAGI GURU SMK KUTAI TIMUR DAN KOTA BONTANG KALIMANTAN TIMUR - Sugianto Sugianto; Rahayu Sri Waskitoningtyas; Casmudi Casmudi (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2023)
The curriculum in the world of education is designed to advance educational goals so that education in Indonesia can keep up with and develop according to the demands of the times. The purpose of this community service is to find out how BIMTEKS assists in the preparation of independent curriculum teaching modules for SMK teachers in East Kutai and Bontang Districts, East Kalimantan. This research is a qualitative research with purposive sampling. PKM of collecting data in community service uses documentation, observation and questionnaire methods. The validity of the data includes: (a) extending the data collection period, (b) making observations, (c) conducting triangulation, and (d) holding discussions with colleagues. From the results of the BIMTEKS study, the assistance in the preparation of the independent curriculum teaching modules for SMK teachers in East Kutai and Bontang Districts, East Kalimantan, went well. This can be seen in the questionnaire on the aspects of the object of implementing the independent curriculum learning plan that the understanding of the policy reaches 90%, the flow of learning objectives is 89%, and the teaching modules is 88%. East Kutai and Bontang Vocational School teachers need to be aware of the changes in the 2013 curriculum to the Independent Curriculum so that there is a need for an increase in teacher innovation and creativity in compiling independent curriculum teaching modules for SMK teachers in East Kutai and Bontang Districts, East Kalimantan which are more interactive for students and use learning methods right